The construction of professional identities in medical writing and fiction, c. 1830s-1910s - Moulds, ASE (2017)
This thesis examines the representation of medical practitioners between the 1830s and 1910s in Britain and its Empire, drawing on the medical press and fiction. Moving away from the notion that practitioners’ identities were determined chiefly by their qualification or professional appointment, it considers how they were constructed in relation to different axes of identity: age, gender, race, and the spaces of practice. Each chapter concentrates on a different figure or professional identity. I begin by looking at the struggling young medical man, before examining metropolitan practitioners (from elite consultants to slum doctors), and the hard-working country general practitioner. I then consider how gender and professional identities intersected in the figure of the medical woman. The last chapter examines practitioners of colonial medicine in British India. This thesis considers a range of medical journals, from well-known titles such as the Lancet and British Medical Journal, to overlooked periodicals including the Medical Mirror, Midland Medical Miscellany, and Indian Medical Record. It also examines fiction by medical authors such as Arthur Conan Doyle and W. Somerset Maugham, and lesser-known figures including Margaret Todd and Henry Martineau Greenhow. I read these texts alongside other contemporary writing (from advice guides for medical men to fiction by lay authors) to scrutinise how ideas about practice were shaped in the medical and cultural imagination. My research demonstrates not only how medical journals fashioned networks among disparate groups of practitioners but also how they facilitated professional rivalries. I reveal the democratising tendency of print culture, highlighting how it enabled a range of medical men and women to write about practice. Ultimately, the thesis develops our understanding of medical history and literary studies by uncovering how the profession engaged with textual practices in the formation of medical identities.